O gaúcho ladrão: abgeato no Rio Grande do Sul no século XIX - Conci, Tiago Ricardo (2015)
This work has as main objective to address critically the cattle rustling, other words, Cattle theft in the field, in the Rio Grande do Sul province, during the nineteenth century.For this, we emphasize the writings of travelers who were in the southern region of the continent during this period, which could report on published works what witnessed in the fields farms and villages where they were, analyzing from different viewpoints the routine and lifestyles of people they met along the way, always printing a particular view of the exotic things that they witnessed in these lands.We treat here, to reconstruct the steps of historiographical formation of Rio Grande do Sul, in order to comb the elements that permeate the imagination about of the gaucho and other groups that started the settlement of this region of Brazil. Added those analysis, besides the literature of the last two centuries, the criminal proceedings, found in the Public Archive of Rio Grande do Sul State, dealing exclusively with the cattle theft crime, sometimes with aggravated in the region of Porto Alegre. Being that researched area had its economic importance based on the exploitation of cattle, first by utility and trade for the hides, then deepened by the beneficiation of the meat with the jerky industry, we will analyze how occurred the processes at cattle rustling crime, checking who they were defendants, and who were the complainants or victims. We'll see what they say witnesses and what arguments used to blame or exonerate the cattle thieves in Rio Grande do Sul. This research was focused on the period immediately before the Farroupilha War (1828-1845) and, especially, during the already deflagrated rebellion (1835-1845), with the appreciation of omissive cases to the traditional historiography. This study does not attempt to the issue of cattle rustling in the RS, but intends to demonstrate how the relationship occurred in the pastoral world, unraveling some myths that recover the figure of contemporary gaucho.